DASAMUKA GANDRUNG : THE IDEA CREATION OF BATIK MOTIFS FOR READY TO WEAR - amriadiyatrohmanna123 anna; Muhammad Arif Jati Purnomo (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2025)
Prabu Dasamuka or Rahwana was the king of Alengka who had ten faces or personalities. The Dasamuka Gandrung story was used to create batik motifs that were then applied to ready to wear clothing. The tragic love story of Dasamuka for Dewi Shinta serves as the main backdrop for the motif creation, with a focus on the deformation of Dasamuka's appearance, applied to primisima cotton fabric through batik writing techniques, dyeing, and the process of creating ready-to-wear clothing. Gustami's creation method uses a three-stage, six-step approach, including story exploration, motif sketch and clothing design, and the realization stage, such as pattern making, batik, dyeing, finishing, sewing, and finishing. This collection is designed for adult women aged 20–40 who need semi-formal casual. It consists of four pieces of clothing, namely Danastri with the Lara Branta motif, Lalita with the Harana motif, Apsari with the Adarma motif, and Cintya with the Susetya motif. This work is expected to introduce the Dasamuka Gandrung puppet character in the form of batik motifs to the wider community as an effort to preserve culture through ready-to-wear.